A SKETCH OF THE VIETNAMESE LANGUAGE AND CULTURE FROM SOUTHEAST ASIAN PERSPECTIVE - Doi, Tran Tri (VNU Journal of Foreign Studies, 2019)
As a Southeast Asian nation, Vietnam is a miniature of the languages and cultures of the region thanks to its possession of the most typical features of the languages and cultures of various Southeast Asiannations. Through description and comparison using an inter-disciplinary approach, the paper points outthat due to Vietnam’s special geographical position, its language and culture do contain phenomena which reflect the boundaries of linguistic and cultural features among different subregions in Southeast Asia. Therefore, Vietnam can be regarded as the intermediary for the linguistic and cultural interchange between the North and the South. In other words, from a cultural-linguistic perspective, Vietnam is considered a gateway or a hub of contact among East Asia, Southeast Asia and South Asia.